PERAN ORGANISASI BANTUAN HUKUM PUSAT ADVOKASI HUKUM DAN HAK ASASI MANUSIA (OBH PAHAM INDONESIA-RIAU) DALAM UPAYA PREVENTIF PERCERAIAN PERNIKAHAN DINI DENGAN KONSEP MEDIASI STUDI PADA KOTA PEKANBARU - Jufri Zulfan; Berri Parma; Betti Rahmasari S (ASAS Law Journal, 2024)
Marriage is a very noble thing because marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the belief in the Almighty God. However, in reality, not all household relationships can run harmoniously. There are various problems in it starting from disagreements, distrust between husband and wife, economic demands, the partner's unstable attitude due to lack of mental and emotional skills at the time of marriage, rights and obligations that are not fulfilled, infidelity and even domestic violence which ultimately results in can trigger arguments which, if not resolved properly, will lead to divorce. This is a problem that we often encounter, one of which is divorce in early marriage. One method that can be used as a form of effort to prevent divorce is by mediation both in court and outside court. Mediation is a dispute resolution process through negotiation or agreement between litigants assisted by a mediator judge who does not have the authority to impose a settlement. The main characteristic of a negotiation or discussion process is that there is no coercion in accepting or rejecting a concept or settlement during the mediation process. Everything must obtain approval from the litigant. In this case, legal aid posts and also Legal Aid Organizations play a role. Legal aid posts are a place for legal services for the community in the form of information, consultation, legal advice, and the preparation of required legal documents.